Pembinaan Kader Posyandu Lansia dalam Peningkatan Pelayanan Lansia dan Pengenalan Aplikasi IT Untuk Kemudahan Petugas dan Lansia - Agustin, Dinni; Ulansari, Ramadani; Yatni, Wanda Tri; Lestari, Sri Diah; Ladawsyah, Ladawsyah (Jurnal Pelayanan dan Pengabdian Kesehatan untuk Masyarakat, 2025)
Elderly Posyandu activities require cadres with adequate competencies in providing health services, data collection, and utilizing information technology. This Community Service Program aims to increase the capacity of Elderly Posyandu cadres through coaching on elderly-friendly services and introducing IT applications to support recording, reporting activities, and browsing health-related applications. The program was held on December 1, 2025, at the Duren Sawit Bersatu RPTRA, Duren Sawit Village, East Jakarta, and was attended by cadres from 17 neighborhood associations (RW) around 100 participants. Methods used included interactive lectures, service simulations, IT application workshops, group discussions, and pre-posttest evaluations. The results of the program demonstrated increased knowledge among cadres regarding Elderly Posyandu management, digital record keeping, and the use of applications as a supporting medium for services. This program can improve the effectiveness and accuracy of elderly services and is recommended for ongoing implementation.